ANALISIS KUALITAS PELAYANAN PROGRAM SEDEKAH NASI BERKAH (SNB) TERHADAP PEMENUHAN KEBUTUHAN PENERIMA MANFAAT DI KABUPATEN JEMBER - wahyuni mayangsari (Universitas Moch. Sroedji, 2026)
The Sedekah Nasi Berkah Program (SNB) is social program a long-term routine program implemented by the RIZKI Amil Zakat Institution by distributing boxes of rice to livelihood fighters on the streets of Jember Regency. The determination of respondents was based on the criteria for the SNB program, namely livelihood fighters, especially online pedicab and motorbike taxi drivers. Sampling was carried out at Kaliwates and Arjasa terminals because these locations met the criteria for asnaf. Before implementing this program, of course there were donors from the RIZKI amil zakat institution who always supported the running of this program. For implementation every Monday and Friday at lunch time or around 13.30 and after Friday prayers. This research aims to analyze beneficiary satisfaction with the SNB or Sedekah Nasi Berkah Program and evaluate obstacles in implementing the program. The approach used was descriptive quantitative with a survey of 13 respondents, the majority of whom worked as pedicab drivers, with an average age of 61 years. The results show that 92% of respondents felt their food needs were met through this program. However, there are deficiencies in socialization, survey data show that 53.8% of respondents did not know about the existence of the program before receiving assistance. Based on these findings, the research recommends increasing socialization, improving implementation time, and program sustainability strategies.